Anaerobic assessment - Sleivert, G.
For many athletes the ability to produce and/or sustain an exercise intensity that exceeds the energy supply capabilities of the aerobic system is an important determinant of success [1-3]. In this respect, energy supply pathways that are capable of producing Adenosine Triphosphate (ATP) independently of oxygen supply (anaerobic metabolism) are critical. Similarly, in sports characterised by intermittent activity, anaerobic energy supply is important since there is a lag in the recruitment of aerobic energy supply at the start of each rest-work transition and initial energy must be derived from anaerobic sources. Two metabolic pathways are the primary contributors to anaerobic ATP production. These systems are commonly referred to as 1. The phosphagen system, also known as the alactic system and 2. anaerobic glycolysis, also known as the lactic acid system. The characteristics of these energy systems are best described using the terminologies of power and capacity. Power refers to the rate of energy supply while capacity refers to the total amount of ATP that the system can supply. The Phosphagen system relies primarily on high energy phosphagens stored in skeletal muscle to produce ATP (Figure 1). Because of this readily available source of energy it is capable of producing ATP at a very high rate (high power) but can only continue ATP supply for a short time since the stores of Creatine Phosphate and ATP in muscle are limited. Therefore it`s capacity is limited. On the other hand the lactic acid system has similar power to the phosphagen system but relies on a more complex series of reactions to break down carbohydrate and form ATP (Figure 2). It can however supply ATP for a longer period of time than the phosphagen system. Both of these anaerobic systems have much lower capacities than the aerobic system but this is compensated for by their higher power. Table 1 summarises the characteristics of the three energy systems. An additional important point is that the energy systems are not recruited sequentially at the start of exercise but concurrently [4- 6].The exercising body does not switch from one energy system to another, rather each energy system supplies a proportion of the required ATP at any given time and this proportion is dependent upon the exact intensity and duration of the exercise bout.